STRATEGIC DECISION MAKING USING SMART APPROACH TO NAVIGATE POST CRISIS RECOVERY AND SUSTAINABILITY : A CASE STUDY OF AN INDONESIAN AQUACULTURE STARTUP - Fikri Adhi Nugraha; Utomo Sarjono Putro (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2025)
Startups have become key drivers of economic growth and innovation worldwide, including in Indonesia. PT. EF, once a leading unicorn in Indonesia that delivered innovative smart feeder technology in aquaculture industry, faced a crisis after financial manipulation and revenue inflation were revealed, leading to massive layoffs and a drastic decline in revenue. This thesis aims to support strategic decision making in the post crisis recovery and sustainability of PT. EF by applying Simple Multi Attribute Rating Technique (SMART). The research methods include both internal and external analyze using frameworks such as VRIO Framework, PESTEL, Porter's Five Forces, as well as SWOT Analyze and TOWS Matrix to generate various recovery strategy alternatives. Data used in this study is obtained from interviews with key stakeholders and secondary data related to the aquaculture industry. Based on these analyze, the alternatives are then evaluated using SMART to provide the most suitable recommendations to ensure sustainable recovery and long term growth for PT. EF. The findings of this research are expected to provide valuable insights for startup in Indonesia in facing crisis challenges and designing effective strategies. This research also contributes to the development of crisis management theory for startups by applying SMART in the context of a company struggling to recover after crisis.